2008
DOI: 10.1002/polb.21523
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the stable and metastable poly(ethylene oxide)–urea complexes in electrospun fibers

Abstract: Solution electrospinning was used for the first time to prepare nanofibers of the stable (α) and metastable (β) complexes between poly(ethylene oxide) (PEO) and urea. Both types of fibers were highly crystalline and presented a large level of molecular orientation. Detailed characterization of the ill‐studied β complex was performed using wide angle X‐ray diffraction (WAXD), infrared spectroscopy, and differential scanning calorimetry (DSC). Results reveal that it possesses a 3:2 PEO:urea stoichiometry and sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 37 publications
7
56
0
Order By: Relevance
“…Many attempts have been made to fabricate nanofibers containing high amount of urea, but the process have been shown problematic. Liu et al in 2008 and Isakov et al in 2010 electrospun PEO and PVA nanofibers containing urea . Both research groups studied the optical characteristics of the urea embedded nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been made to fabricate nanofibers containing high amount of urea, but the process have been shown problematic. Liu et al in 2008 and Isakov et al in 2010 electrospun PEO and PVA nanofibers containing urea . Both research groups studied the optical characteristics of the urea embedded nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that adding urea into the PEO film promotes crystallinity via formation of the highly crystallized complexes. Particularly, formation of specific complexes between PEO and urea was reported in 37,38 for the two PEO:urea molar ratios 3:2 and 4:9. The two complexes were suggested to be of a layered or channel type.…”
Section: Effects Of Additives On the Properties Of Polymer Electrolyte-mentioning
confidence: 99%
“…1(a), the N-H stretching bands in the spectrum of the film with a urea concentration of 0.1 M were observed at lower frequencies compared to those in the spectra of the film with urea concentrations of more than 0.2 M. This indicates that the complex with a urea concentration of 0.1 M consists mainly of the β-phase and that the other complexes with urea concentrations of more than 0.2 M consist mainly of the α-phase [9]. Therefore, the β-phase of the complex transforms into the α-phase with an increase in the urea concentration [4]: this transformation is hereafter, referred to as the β-α transition.…”
Section: Resultsmentioning
confidence: 83%
“…Some parts of the β-phase complexes can be transformed into α-phase complexes by increasing the urea mole fraction or by heating. The β-α transition of PEO-urea complexes and their structural phase diagrams have been intensively studied [2,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%